The Effects of Dietary ω -3 and ω -6 Fatty Acids on Nutrient Utilization and Growth Performance in Sahiwal Heifers - Kumar, Sushil; Sihag, Sajjan; Sihag, Zile Singh; Patil, C S; Dhaka, Surender Singh; Pandey, Anand Kumar (Indian Journal of Animal Nutrition, 2020)
The study was conducted to evaluate the effect of dietary supplementation with omega-3 and omega-6 rich oil on nutrient utilization, growth performance and pubertal age in Sahiwal heifers. Eighteen healthy sahiwal heifers of average 18.33±1.14 month’s age and 194±4.16 kg body weights were randomly assigned to 3 treatment groups viz T1, T2 & T3 with 6 animals in each. Heifers were individually fed as per ICAR (2013) diets of chopped wheat straw, green fodder and concentrate mixture. The concentrate mixtures fed to the heifers under treatment group T2 and T3 were supplemented with omega-6 fatty acid rich soybean oil and omega-3 fatty acid rich linseed oils @ 3.5 percent, respectively. To make the rations iso-caloric, palm oil @ 3.5 percent was supplemented in the concentrate mixture of heifers in control group (T1). All the concentrate mixtures were isonitrogenous. Daily DMI was significantly (P<0.05) higher in heifers fed linseed oil supplemented concentrate mixture as compared to others. Total body weight gain and ADG was significantly (P<0.05) higher T3 than T2 and control heifers. The OMD was significantly (P<0.05) improved in groups fed omega-6 and omega-3 rich oils as compared to control. The CP, DCP and TDN percent; and TDN intake did not differ among different dietary treatments. The FCE improved upon supplementation of omega-3 rich FA oil, but non-statistically. Feeding linseed oil resulted in significant (P<0.05) reduction in the estrous age of sahiwal heifers as compared to others. The total dry matter intake up to first estrous was reduced by 32.12 and 12.77 percent in T3 and T2, respectively, as compared to control (T1). Similarly, total concentrate mixture intake up to attainment of heifers’ pubertal age in omega-3 rich linseed oil and omega-6 rich soybean oil fed group reduced by 38.82 and 16.11 percent, respectively, over control diet. The study deduced that omega-3 fatty acid supplementation reduces pubertal age of sahiwal heifers.